Growth of public consumption in Austria: Testing Wagner's law and Baumol's cost disease - Monika Köppl-Turyna; Dénes Kucsera; Reinhard Neck (Agenda Austria, 2017)
In this paper, we analyze the development of public consumption expenditure in Austria starting in the 1940s. We focus our attention on two hypotheses as to why public consumption expenditure has been constantly increasing: Wagner's law and Baumol's cost disease. The estimated income elasticity of demand for public consumption expenditure of 0.85 suggests that Wagner's law is not confirmed. In contrast, price-inelastic demand combined with a strong increase in the prices of public services relative to private goods suggest that Baumol's cost disease is at work. A counterfactual exercise shows that in the absence of the rise in the relative price of publicly provided goods, current public consumption would equal 15.98% of GDP instead of the actually observed 19.92%. We further confirm the main observations using a cointegration model.
Keywords: H11; H50; 330; Wagner's law; Baumol's cost disease; Austria; public consumption